Dispersing and semi-flat bands in the wide band gap two-dimensional semiconductor bilayer silicon oxide. (29th April 2021) - Kremer, Geoffroy; Camilo Alvarez-Quiceno, Juan; Pierron, Thomas; González, César; Sicot, Muriel; Kierren, Bertrand; Moreau, Luc; Rault, Julien E; Le Fèvre, Patrick; Bertran, François; Dappe, Yannick J; Coraux, Johann; et al.
Abstract: Epitaxial bilayer silicon oxide is a transferable two-dimensional material predicted to be a wide band gap semiconductor, with potential applications for deep UV optoelectronics, or as a building block of van der Waals heterostructures. The prerequisite to any sort of such applications is the knowledge of the electronic band structure, which we unveil using angle-resolved photoemission spectroscopy and rationalize with the help of density functional theory (DFT) calculations. We discover dispersing bands related to electronic delocalization within the top and bottom planes of the material, with two linear crossings reminiscent of those predicted in bilayer AA-stacked graphene, and semi-flat bands stemming from the chemical bridges between the two planes. This band structure is robust against exposure to air, and can be controlled by exposure to oxygen. We provide an experimental lower-estimate of the band gap size of 5 eV and predict a full gap of 7.36 eV using DFT calculations.